Research review on improving the efficiency of multimodal transportation based on technological solutions - M. I. Malyshev (Научный вестник МГТУ ГА, 2020)
During the process of analyzing Russian and foreign studies in the field of multimodal cargo transportation, existing methods for improving the efficiency of the multimodal transport system are considered. Improving efficiency of multimodal transportation today is possible due to the optimization of the interaction system between the used modes of transport and transportation of goods. Cost reduction, optimization of cargo terminals, the formation and development of the transport corridors network also play an important role in improving this type of transportation. The use of the new capabilities of satellite navigation, as well as the importance of reducing the environmental load and fuel economy should not be underestimated. The minimization of risks throughout the field of multimodal transportation, the improvement of the legislative framework and document management processes are important. To solve these problems, experts propose methods for the operational management of cargo delivery and expedited transportation. Based on these methods, the place of transport logistics in the process of bringing goods to the consumer during multimodal transportation is determined. A methodology for designing a multimodal transport network has been developed, this methodology involves the formation and development of transport corridors, taking into account new conditions for the globalization of transportation. Researches on the organization of transportation using multimodal transport units and technologies (containers, contrailers, "running highway") have been conducted. Based on the theory of controlled networks and integer linear programming methods, the experts developed mathematical models for the distribution of cargo flows, the choice of the most favorable transportation routes, ideal loading of rolling stock, and transportation of goods using the best forwarding algorithm. Methods are proposed for assessing the maximum capacity of the transport network and predicting the interference of weather conditions in the process of goods transportation, based on the Ford-Fulkerson theorem on the maximum flow and minimum cross section and the use of the mathematical apparatus of Markov chains. As a result of the analysis, it was concluded that the lack of a universal methodology for managing multimodal transportation processes on the basis of a telecommunication platform requires the formulation and solution of the important scientific and practical problem - the development of popular organizational and management methods, technological solutions to ensure the effectiveness of multimodal transportation. The totality of the tasks to be solved in this case has important socio-economic significance for the Russian Federation.